2022
DOI: 10.3389/fimmu.2022.982986
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3+ regulatory T cells and the immune escape in solid tumours

Abstract: FOXP3+ regulatory T (Treg) cells play critical roles in establishing the immunosuppressive tumour microenvironment, which is achieved and dynamically maintained with the contribution of various stromal and immune cell subsets. However, the dynamics of non-lymphoid FOXP3+ Treg cells and the mutual regulation of Treg cells and other cell types in solid tumour microenvironment remains largely unclear. In this review, we summarize the latest findings on the dynamic connections and reciprocal regulations of non-lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 191 publications
0
11
0
3
Order By: Relevance
“…Regulatory T cells (Tregs), a class of immunosuppressive cells, are responsible for tumor cell immune escape. [ 37 , 38 ] Therefore, Treg infiltration in mouse tumors was further analyzed. The results showed that the proportion of Tregs in the mice treated with ES@CuO+PD‐1 was significantly lower than that in the control mice, while the proportion of CD3 + CD4 + T cells did not change among the groups (Figure S20 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory T cells (Tregs), a class of immunosuppressive cells, are responsible for tumor cell immune escape. [ 37 , 38 ] Therefore, Treg infiltration in mouse tumors was further analyzed. The results showed that the proportion of Tregs in the mice treated with ES@CuO+PD‐1 was significantly lower than that in the control mice, while the proportion of CD3 + CD4 + T cells did not change among the groups (Figure S20 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that CTLA-4 is constitutively expressed on Treg cells [44]. FOXP3+ Treg cell-mediated immunosuppression is also implemented by the release of a variety immunosuppressive cytokines, e.g., IL-10, IL-35 and TGF-β [42,45]. The mechanisms described above demonstrate that FOXP3+ Treg cells promote immune escape from cancer.…”
Section: Presence Of Foxp3 In the Tmementioning
confidence: 97%
“…The FOXP3+ Tregs are known for their immunosuppressive functions and their presence in the TME may suppress the anti-tumor immune response by the inhibition of the activity of cytotoxic T cells and other effector immune cells, contributing to immune evasion by the cancer cells [38,41] (Figure 3). The occurrence of an immunosuppressive TME promotes tumor growth and progression; for this reason, the FOXP3+ Tregs presence has been associated with a poor prognosis in various solid tumors [42], including NSCLC (HR: 3.91 and p < 0.001) [43]. In addition, among patients with node-negative NSCLC (N0), tumor-infiltrating FOXP3+ Tregs were positively correlated with intratumor COX-2 expression and were associated with a worse recurrence-free survival [10].…”
Section: Presence Of Foxp3 In the Tmementioning
confidence: 99%
See 2 more Smart Citations